Characterization of Long Non-coding RNAs Modified by m6A RNA Methylation in Skeletal Myogenesis - Xie, Shu-Juan; Tao, Shuang; Diao, Li-Ting; Li, Pan-Long; Chen, Wei-Cai; Zhou, Zhi-Gang; Hu, Yan-Xia; Hou, Ya-Rui; Lei, Hang; Xu, Wan-Yi; Chen, Wen-Jie; Peng, Yan-Wen; et al. (Frontiers in Cell and Developmental Biology, 2021)
Proper development of mammalian skeletal muscle relies on precise gene expression regulation. Our previous studies revealed that muscle development is regulated by both mRNA and long noncoding RNAs (lncRNAs). Accumulating evidence has demonstrated that N6-methyladenosine (m6A) plays important roles in various biological processes, making it essential to profile m6A modification on a transcriptome-wide scale in developing muscle. Patterns of m6A methylation in lncRNAs in developing muscle have not been uncovered. Here, we reveal differentially expressed lncRNAs and report temporal m6A methylation patterns in lncRNAs expressed in mouse myoblasts and myotubes by RNA-seq and methylated RNA immunoprecipitation (MeRIP) sequencing. Many lncRNAs exhibit temporal differential expression, and m6A-lncRNAs harbor the consensus m6A motif “DRACH” along lncRNA transcripts. Interestingly, we found that m6A methylation levels of lncRNAs are positively correlated with the transcript abundance of lncRNAs. Overexpression or knockdown of m6A methyltransferase METTL3 alters the expression levels of these lncRNAs. Furthermore, we highlight that the function of m6A genic lncRNAs might correlate to their nearby mRNAs. Our work reveals a fundamental expression reference of m6A-mediated epitranscriptomic modifications in lncRNAs that are temporally expressed in developing muscle.